2010
DOI: 10.1016/j.pharmthera.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors regulate the expression of vascular endothelin receptors

Abstract: Cardiovascular disease remains as the leading cause of death in the developed world.However, there is limited knowledge about how cardiovascular risk factors actually cause vascular disease. Traditional cardiovascular risk factors include increased circulating levels of low-density lipoproteins, cigarette smoking and hypertension (both strongly related to arterial wall injury), inflammation and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 118 publications
0
29
0
Order By: Relevance
“…Consistent with this role of endothelins, increased EDN1 and EDNRA levels have been reported following rupture of IAs (20)(21)(22). In addition, hypertension and smoking, both well-established risk factors of IA pathogenesis, have been shown to alter the expression of endothelins (23).…”
Section: −7mentioning
confidence: 55%
“…Consistent with this role of endothelins, increased EDN1 and EDNRA levels have been reported following rupture of IAs (20)(21)(22). In addition, hypertension and smoking, both well-established risk factors of IA pathogenesis, have been shown to alter the expression of endothelins (23).…”
Section: −7mentioning
confidence: 55%
“…Interestingly, up-regulation of ETB2 receptors was also found in in vitro organ culture model of rat mesenteric arteries after long-term exposure (1-5 days) to serum-free medium (Adner et al, 1998). Recent studies demonstrated that addition of lipid-soluble cigarette smoke particles ( Huang et al, 2010 andXu et al, 2008), or lowdensity lipoprotein (Xu et al, 2010) led to increased ETB2 receptors expression and/or enhanced ETB2 receptor-mediated vasoconstriction. These in vitro findings expanded the knowledge regarding the importance of ETB2 receptor up-regulation in the development of atherosclerotic CVDs.…”
Section: Introductionmentioning
confidence: 86%
“…However, the role of ETB receptors may switch from vasodilatation (relaxing phenotype, termed ETB1) to vasoconstriction (contractile phenotype, termed ETB2) under certain pathophysiological conditions ( Stenman et al, 2002 andXu et al, 2010). The different subpopulations of ETB receptors exert distinct biological effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK10 and several other genes are also components of the MAPK module because the focal adhesion pathway and the MAPK signaling pathway greatly overlap. Recently, researchers have suggested that MAPK may be the key node linking cardiovascular insulin resistance, vascular endothelial dysfunction and pathogenesis of atherosclerosis (Liu and Cao, 2009;Xu et al, 2010).…”
Section: Verification By Literature Retrievalmentioning
confidence: 99%